A rapid and visual detection assay for Senecavirus A based on recombinase-aided amplification and lateral flow dipstick - Song, Yiwan; Fang, Yiqi; Zhu, Shuaiqi; Wang, Weijun; Wang, Lianxiang; Chen, Wenxian; He, Yintao; Yi, Lin; Ding, Hongxing; Zhao, Mingqiu; Fan, Shuangqi; Li, Zhaoyao; et al. (Frontiers in Cellular and Infection Microbiology, 2024)
BackgroundSenecavirus A (SVA) is a newly pathogenic virus correlated with the acute death of piglets and vesicular lesions in pigs. The further prevalence of SVA will cause considerable economic damage to the global pig farming industry. Therefore, rapid and accurate diagnostic tools for SVA are crucial for preventing and controlling the disease.MethodsWe designed multiple primer pairs targeting the most conserved region of the SVA 3D gene and selected those with the highest specificity. Nfo-probes were subsequently developed based on the highest specificity primer pairs. Subsequently, the recombinase-assisted amplification (RAA) reaction was completed, and the reaction temperature and duration were optimized. The RAA amplicons were detected using a lateral flow device (LFD). Finally, a rapid and intuitive RAA-LFD assay was established against SVA.ResultsThe SVA RAA-LFD assay can be performed under reaction conditions of 35°C within 17 minutes, with results observable to the naked eye. We then evaluated the performance of this method. It exhibited high specificity and no cross-reaction with the other common swine pathogens. The lowest detectable limits of this method for the plasmid of pMD18-SVA-3D, DNA amplification product, and viral were 3.86×101 copies/µL, 8.76×10-7 ng/µL, and 1×100.25 TCID50/mL, respectively. A total of 44 clinical samples were then tested using the RAA-LFD, PCR, and RT-qPCR methods. The results demonstrated a consistent detection rate between the RAA-LFD and RT-qPCR assays.ConclusionThe SVA RAA-LFD assay developed in our study exhibits excellent specificity, sensitivity, and time-saving attributes, making it ideally suited for utilization in lack-instrumented laboratory and field settings.